The importance of horizontal fit of university student jobs for future job quality - I.J.M. Van der Heijden, Beatrice; Le Blanc, Pascale M; Hernandez, Ana; Gonzalez-Roma, Vicente; Yeves, Jesus; Gamboa, Juan P (Career development international, 2019)
Purpose The purpose of this paper is to gain a better understanding of the antecedents of the quality of graduates’ jobs when they enter the job market after university graduation. Design/methodology/approach Survey data collected from 173 Spanish bachelor and master’s degree university graduates at two time points (two months before and six months after graduation, approximately) were analyzed by means of path analysis. Findings A moderated mediation model was tested, where the relationship between the horizontal fit (HF) between the university degree subject and the student’s job and the quality of the graduate’s job after graduation is mediated by self-perceived employability and moderated by the time devoted to a student job. Results showed that the relationship between HF and job quality was partially mediated by self-perceived employability. However, contrary to the proposed hypothesis, this relationship did not depend on the time devoted to a student job. Originality/value This study contributes to improving the understanding about how and why university students’ work experience is related to the quality of their jobs as fresh graduates.